2011
DOI: 10.1039/c1sm05439b
|View full text |Cite
|
Sign up to set email alerts
|

Control of spontaneous spiral formation in a zwitterionic micellar medium

Abstract: The transition from planar fronts, trigger waves or solitary pulses to spirals in excitable media, has\ud attracted increasing interest in the past few decades, mainly because of its relevance for biological and\ud medical applications. In this paper we describe a new and convenient method for spiral generation\ud starting from symmetric wavefronts. By using the micelle-forming zwitterionic surfactant N-tetradecyl-\ud N,N-dimethylamine oxide in a Belousov–Zhabotinsky solution, it is possible to control to a la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 50 publications
1
9
0
Order By: Relevance
“…As the reaction proceeds, the production of Br 2 saturates S and can actively return to participate in the oscillatory mechanism. Similar properties of the BZ medium have been recently reported by Rossi et al, 25,26 who found that a zwitterionic surfactant (N-tetradecyl-N,N-dimethylamine oxide, C 14 DMAO) can form a charge transfer complex with Br 2 , thus acting as the sequestrating species S used in the present theoretical model (the value of the rate constant k 10 for the kinetic step 5 is inspired to this system). Due to the interaction between C 14 DMAO and Br 2 , an unusual oxidized induction period appears in the ferroin-catalyzed BZ reaction, whose duration increases with the surfactant concentration (typically in the range 0.003−0.008 M).…”
supporting
confidence: 82%
See 1 more Smart Citation
“…As the reaction proceeds, the production of Br 2 saturates S and can actively return to participate in the oscillatory mechanism. Similar properties of the BZ medium have been recently reported by Rossi et al, 25,26 who found that a zwitterionic surfactant (N-tetradecyl-N,N-dimethylamine oxide, C 14 DMAO) can form a charge transfer complex with Br 2 , thus acting as the sequestrating species S used in the present theoretical model (the value of the rate constant k 10 for the kinetic step 5 is inspired to this system). Due to the interaction between C 14 DMAO and Br 2 , an unusual oxidized induction period appears in the ferroin-catalyzed BZ reaction, whose duration increases with the surfactant concentration (typically in the range 0.003−0.008 M).…”
supporting
confidence: 82%
“…In order to show that the interplay between a phase and a target wave can effectively represent a driving mechanism for the spontaneous nucleation of spirals in a real system with a quasi-two-dimension geometry, we performed experiments with the BZ−C 14 DMAO system which, as mentioned above, has been successfully introduced as an experimental example where a kinetic interaction of the type described by the reaction step 5 takes place. 25,26 As extensively discussed in ref 26, by varying the concentrations of the chemicals in solution, specifically [C 14 DMAO] and [NaBr], we can control to a certain extent the transition of target waves to spirals. Figure 5a illustrates the generation of two counter rotating spirals from a circular wave when [C 14 DMAO] = 5 × 10 −3 .…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
“…2. Act as a catalyst in nucleophilic, dephosphorylation, photocatalytic oxidation and Belousov-Zhabotinsy reaction (Bunton et al, 1987(Bunton et al, , 1989Marcì et al, 2003;Rossi et al, 2008Rossi et al, , 2011.…”
Section: -[(3-cholamidopropyl)dimethylammonio]-1-propanesulfonate (Chaps)mentioning
confidence: 99%
“…Experimentally, we introduce sodium dodecyl sulphate (SDS) anionic surfactant in the BZ medium and vary its concentration above the critical micelle concentration (CMC) to increase the solution viscosity. SDS was found to slightly alter the kinetics of the BZ reaction, without changing the oscillation mechanism and without introducing new dynamical features 37 , conversely, for example, to the case of the zwitterionic surfactant N-tetradecyl-N,N-dimethylamine oxide that was found to cause an induction period prior the onset of regular oscillations [38][39][40] . Therefore, the use of SDS impacts mainly the viscosity of the solution that, in turn, affects the onset of natural convection.…”
Section: Introductionmentioning
confidence: 97%